Identification of the Lymantria dispar Nucleopolyhedrovirus Envelope Fusion Protein Provides Evidence for a Phylogenetic Division of the Baculoviridae - Pearson, Margot N. (American Society for Microbiology, 2000)
The complete genome sequences of a number of diverse members of the Baculoviridae including both nucleopolyhedroviruses (NPVs) and granuloviruses (GVs) revealed that they lack a homolog of GP64, the envelope fusion protein of the budded form of Autographa californica multinucleocapsid NPV (AcMNPV) and its close relatives. Computer-assisted analyses of the genome of one of these viruses, Lymantria dispar MNPV (LdMNPV), revealed a single open reading frame (ld130) whose product had the predicted properties of a membrane protein. Characterization of the localization of the products of the full-length ld130 gene and of an ld130-enhanced green fluorescent protein gene (egfp) fusion using both immunofluorescence and fluorescence microscopy revealed that LD130 accumulates at the plasma membranes of cells infected with LdMNPV or transfected with ld130-egfp. In addition, cells transfected with either ld130 or ld130-egfp or infected with wild-type virus undergo membrane fusion at pH 5. Western blot analyses indicate that LD130 is present in infected cells as an 83-kDa protein and is also present in budded virions as a protein doublet containing bands of 81 and 83 kDa. Tunicamycin treatment of infected cells resulted in an immunoreactive band of about 72 kDa, indicating that LD130 is N-glycosylated. Whereas the distribution of gp64 appears to be confined to a relatively closely related group of NPVs, homologs of ld130 are present in a diverse number of both NPVs and GVs. This suggests that LD130 may be the primordial baculovirus envelope fusion protein.